Positive Feedback Cycle of TNFα Promotes Staphylococcal Enterotoxin B-Induced THP-1 Cell Apoptosis - Zhang, Xiaopeng; Shang, Weilong; Yuan, Jizhen; Hu, Zhen; Peng, Huagang; Zhu, Junmin; Hu, Qiwen; Yang, Yi; Liu, Hui; Jiang, Bei; Wang, Yinan; Li, Shu; et al. (Frontiers in Cellular and Infection Microbiology, 2016)
Staphylococcal enterotoxin B (SEB) has been demonstrated to be of importance in Staphylococcus aureus related diseases, such as atopic dermatitis (AD). Dysregulated apoptosis in AD is remarkable, and SEB can induce apoptosis of various cell types. However, the mechanisms by which SEB induces apoptosis and influences disease processes remain unclear. In this study, the recombinant SEB-induced THP-1 monocyte apoptosis was demonstrated in the absence of preliminary cell activation in a time- and dose-dependent manner. SEB could up-regulate the expression of tumor necrosis factor alpha (TNFα) in THP-1 cells and induce apoptosis via an extrinsic pathway. TNFα could in turn increase the expression of HLA-DRa, the SEB receptor on the cell surface. As a result, a positive feedback cycle of TNFα was established. TNFα expression and SEB-induced apoptosis were decreased by knocking down the expression of either HLA-DRa or TNFR1. Therefore, the feedback cycle of TNFα is crucial for SEB functions. This work provides insights into the mechanisms of SEB-induced monocyte apoptosis and emphasizes the major role of TNFα in future related studies.